Quantitative trait loci mapping for resistance to maize streak virus in F2: 3 population of tropical maize - Garcia-Oliveira, A.L.; Menkir, A.; Kumar, P. Lava; Azuh, V.; Jacob, O.O.; Gedil, Melaku A (Springer, 2020)
Maize streak virus (MSV) continues to be a major biotic constraint for maize production throughout Africa. Concerning the quantitative nature of inheritance of resistance to MSV disease (MSVD), we sought to identify new loci for MSV resistance in maize using F2:3 population. The mapping population was artificially inoculated with viruliferous leafhoppers under screenhouse and evaluated for MSVD resistance. Using 948 DArT markers, we identified 18 quantitative trait loci (QTLs) associated with different components of MSVD resistance accounting for 3.1–21.4% of the phenotypic variance, suggesting that a total of eleven genomic regions covering chromosomes 1, 2, 3, 4, 5 and 7 are probably required for MSVD resistance. Two new genomic regions on chromosome 4 revealed the occurrence of co-localized QTLs for different parameters associated with MSVD resistance. Moreover, the consistent appearance of QTL on chromosome 7 for MSVD resistance is illustrating the need for fine-mapping of this locus. In conclusion, these QTLs could provide additional source for breeders to develop MSV resistance.